The Need Analysis of Teaching Materials for the Struggle of Todung Sutan Gunung Mulia History to Improve Political Awareness of the Students in SMAK Diponegoro Blitar Town - Jeffry Dwi Kurniawan; Muhammad Akhyar; Susanto Susanto (BIRCU, 2019)
This study was aimed to analyze the quality of the use of teaching materials of history based on the materials relevance with the students’ competency, the students’ political awareness, and the need of teaching materials of history of the struggle of Todung Sutan Gunung Mulia. This study used a qualitative method (case study) to obtain the data about the use of teaching materials of history and the students’ political awareness at SMAK Diponegoro Blitar. The results of the research showed that 1) teaching materials that was used had not supported the political awareness, 2) the students’ political awareness was still low, and 3) teaching materials of history of Todung Sutan Gunung Mulia was needed to improve the students’ political awareness at SMAK Diponegoro Blitar.